Normal Coordinate Analysis and Spectral Analysis of Cyclohexanone Oxime - Mani, P.; Suresh, S.; Revathi, C. (Asian Journal of Chemistry, 2010)
FTIR and FTR spectra of cyclohexanone oxime have been recorded in the regions 4000-200 and 4000-30 cm-1, respectively. The vibrational analysis has been carried out by assuming Cs symmetry. The observed frequencies were assigned to various modes of vibrations on the basis of intensity, frequencies from allied molecules and normal coordinate calculations. The potential energy distribution associated with normal modes are also reported here. The assignments of fundamental vibrational frequencies for cyclohexanone oxime agree with the calculated frequencies. The different chemical environments of the protons were ascertained using 1H NMR spectra and the purity of the compound was confirmed by mass spectral data.